Spike Electrode-Based DBD Reactor for Improved Electric Discharge Power Toward Better Diesel Engine Exhaust Treatment at Low Applied Voltage - Bhattacherjee S.; Mohapatro S. (My University, 2025)
Concern has been raised recently by the increasing usage of diesel engines in both the automotive and industrial sectors. Due of the strict emission regulations, it will be challenging to economically manage exhaust using solely conventional methods. Alternative methods such as electric discharge-based diesel engine exhaust (DEE) treatment have become more popular; however, because this technology requires high voltage, its application in automobiles is restricted. In this study, a dielectric barrier discharge (DBD) reactor with a spike electrode arrangement is suggested for the treatment of diesel exhaust. NOX removal from 5-kVA DEE is evaluated using two types of symmetrical and asymmetrical spike electrode-based DBD reactors in comparison to plane electrode-based DBD. It has been found that while using 50-Hz ac at a lower applied voltage, a spike-configured electrode can inject more power than a plane electrode. As a result, nitric oxides are removed more effectively at lower applied voltages. This research will contribute to the implementation of non-thermal plasma (NTP)-based exhaust treatment in the automotive industry. When compared to other types of electrodes at lower applied voltages, the asymmetrical spike electrode-based DBD with a 10-mm spacing between spikes demonstrated superior NO elimination. Simulation study for electric field of each electrode configuration was conducted using COMSOL Multiphysics and it was in line with the experimental results. The experiments were conducted at 5 L/min keeping the load on the diesel engine at 80%. © 1973-2012 IEEE.